Short‐ and long‐term effects of gestational diabetes mellitus on healthcare cost: a cross‐sectional comparative study in the ATLANTIC DIP cohort. Issue 4 (12th January 2015) - Danyliv, A.; Gillespie, P.; O'Neill, C.; Noctor, E.; O'Dea, A.; Tierney, M.; McGuire, B.; Glynn, L. G.; Dunne, F.
Abstract: Aims: This paper examines the association between gestational diabetes mellitus and costs of care during pregnancy and 2–5 years post pregnancy. Methods: Healthcare utilization during pregnancy was measured for a sample of 658 women drawn from the Atlantic Diabetes in Pregnancy (ATLANTIC DIP) network. Healthcare utilization 2–5 years post pregnancy was assessed for a subsample of 348 women via a postal questionnaire. A vector of unit costs was applied to healthcare activity to calculate the costs of care at both time points. Differences in cost for women with gestational diabetes mellitus compared with those with normal glucose tolerance during the pregnancy were examined using univariate and multivariate regression analyses. Results: Gestational diabetes mellitus was independently associated with an additional €817.60 during pregnancy (€1192.1 in the gestational diabetes mellitus group, €511.6 in the normal glucose tolerance group), in the form of additional delivery and neonatal care costs, and an additional €680.50 in annual healthcare costs 2–5 years after the index pregnancy (€6252.4 in the gestational diabetes mellitus group, €5434.8 in the normal glucose tolerance group). Conclusions: These results suggest that gestational diabetes mellitus is associated with increased costs of care during and post pregnancy. They provide indication of the associated cost that can be avoided or reduced by the screening, prevention and management of gestational diabetes mellitus in pregnancy. These estimates are useful for further studies that examine the cost and cost‐effectiveness of such programmes.